Microbiological quality assessment of potential pathogenic bacteria and multidrug resistance patterns in commercial electrolyte drinks in Dhaka, Bangladesh - Sananda Saha; Ayesha Maliha Khan; Fahim Kabir Monjurul Haque (PLoS ONE, 2026)
Local electrolyte drinks in Bangladesh are produced without approval from the Bangladesh Standards and Testing Institution (BSTI). Hence, this study aimed to identify foodborne bacteria from electrolyte drinks and their antimicrobial resistance profiles to assess microbiological safety. A total of 40 electrolyte drink samples, representing 9 local brands in Dhaka, were evaluated for microbiological quality. Bacteria were present in all samples. Around 40% of the samples exceeded the aerobic plate count limit established by the Food and Drug Administration (FDA). Additionally, 55% of the samples tested positive for fecal contamination, surpassing the accepted limit set by the Food and Agriculture Organization of the United Nations (FAO). Both Gram-negative ( Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and Vibrio spp .) and Gram-positive ( Staphylococcus aureus, Staphylococcus epidermidis , and Listeria spp .) bacteria were identified. Each sample contained more than one bacterial species. A total of 110 isolates from each culture-positive sample were screened for antimicrobial susceptibility. Multidrug resistance varied among all Gram-positive and Gram-negative bacterial species. The highest level of resistance was seen in broad-spectrum antibiotics (amoxicillin, ampicillin, ceftriaxone, cefotaxime, and cefepime). About 28% of Gram-positive and 19% of Gram-negative bacteria were hemolytic. Coagulase was found in 34% of the Staphylococcus aureus isolates. Moreover, 26% of the Gram-positive and 30% of the Gram-negative isolates were found to be resistant to human serum treatment. Such resistant bacteria found in popular electrolyte drinks thus represent a major health risk.